Performance assessment of agroecology in India - Krishnan, Smitha; Gupta, Shweta; Malaiappan, Sudharsan; Singh, Sonali; Kumar, Gopal; Alvi, Muzna; Shijagurumayum, Meghajit; Samaddar, Ayan; Sikka, Alok (2024)
The main objective of the HOLPA (Holistic Localized Performance Assessment) survey is to gather baseline information on the agronomic, environmental, social and economic performance outcomes of fields, farms, landscapes and food systems to understand the agroecological transition in the context of Mandla. While the survey expects to find useful information on farming practices that bring about positive outcomes that are relevant from an agro-ecological and socio-economical perspective, the survey has also helped us identify the main barriers and enablers to agroecological transition in Mandla. Through deliberations with the team based on the V2A, follow-up interactions with the partners and the original objectives of the Agroecology Initiative, we have identified a set of research questions listed below. We have explored the first 3 of these research questions and presented them in the report. 1. Do agroecological farming practices enhance insects that render important ecosystem services that enhance farm productivity? (LISP) 2. Are farm based observations (one time visit) sufficient to evaluate farm diversity or green cover or are there other tools that can help with providing a much more realistic picture? 3. How do the current soil conditions in the targeted area align with the requirements for supporting an agroecological transition, and what specific interventions, if any, are necessary to improve soil health for successful implementation? 4. What is the current exposure of farmers to agroecological farming methods through training and workshops (or interventions)? Have these trainings helped in enhancing on-farm agroecological practices? 5. What determines food security and dietary diversity of farming communities? Does agroecological farming methods facilitate nutritional security in Mandla? 6. What is the impact of past interventions related to commons restoration and soil conservation on the status of agroecology in Mandla? Do these interventions improve water security and soil health for smallholder farmers, and is there sufficient water availability year-round to sustain these practices?